High-capacity hydrogen storage alloy and preparation method thereof
Through rare earth refining and metal element doping and optimized heat treatment process, the problem of impurities in the hydrogen storage performance of ferrovana ferroalloy hydrogen storage alloy is solved, and a high-capacity and low-cost hydrogen storage alloy is achieved.
Patent Information
- Application Number
- CN202510131362.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ferrovana vanadium hydrogen storage alloys have impurities that affect hydrogen storage performance, and the preparation process is complex and costly, resulting in low hydrogen storage capacity and limited application.
Rare earth refined vanadium ferroalloy is used to dopant metal elements, and the heat treatment process is optimized to reduce the content of impurity elements and improve the hydrogen storage performance of the alloy.
The maximum hydrogen absorption and effective dehydrogenation amount of the hydrogen storage alloy are significantly improved, with the maximum hydrogen absorption of more than 3.3 wt.%, and the effective hydrogen absorption of more than 2 wt.%, and the cost of the alloy is reduced.
Smart Images

Figure CN119571135A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage materials, in particular to a high-capacity hydrogen storage alloy and a preparation method thereof. Background Art
[0002] Hydrogen can be produced from renewable energy sources such as hydropower, wind power, solar energy, biomass energy and geothermal energy, as well as non-renewable energy sources such as coal, natural gas and nuclear energy. As a secondary energy source with abundant sources, green and low carbon, it is becoming an important strategic choice for the global energy transformation and development. At present, the storage methods of hydrogen include high-pressure gaseous hydrogen storage, liquid hydrogen storage, solid hydrogen storage, etc. At present, high-pressure gaseous hydrogen storage is the most widely used hydrogen storage method, but due to its high hydrogen storage pressure (35MPa~70MPa) and easy leakage of hydrogen, the safety of hydrogen storage in this way is insufficient. Liquid hydrogen storage has the advantages of high weight density and low pressure, but due to the low boiling point of liquid hydrogen, its cooling technology needs to reach a very low temperature, and the application cost is high. Considering the hydrogen economy, the requirements for safety, efficiency, economy, lightness and compactness of hydrogen storage systems are increasing. Solid hydrogen storage, especially metal hydride hydrogen storage, has the advantages of high volume hydrogen storage density, high safety, low use pressure and recyclability, and is expected to become an effective means to solve the problems that restrict the development of hydrogen storage and transportation. At present, it has gradually played an important role in hydrogen purification, hydrogen refueling stations and fuel cell vehicle applications.
[0003] Vanadium (V)-based BCC hydrogen storage alloys can be developed into a safe system because of their characteristics of being difficult to crush and having a low possibility of ignition and self-ignition. When metal V absorbs hydrogen, two types of hydrides, V2H and VH2, can be generated. Under room temperature conditions, the theoretical hydrogen storage capacity of V is as high as 3.80 wt.%, but the equilibrium hydrogen pressure of V2H is extremely low (about 10-9MPa), making it difficult to utilize the hydrogen release reaction of V2H-V. In fact, the amount of hydrogen released by the VH2-V2H reaction that can be utilized is only about 1.90 wt.%, and the effective hydrogen storage capacity is low. In addition, pure V metal is difficult to activate (the surface VH has strong action ability) and metal vanadium is expensive. At present, many hydrogen storage alloys are doped with elements such as Ti, Cr, Mn, Fe, and rare earth elements to improve the activation performance of V-based BCC hydrogen storage alloys, adjust the hydrogen absorption and desorption platform pressure, and reduce costs, such as patents CN115612903A, CN111636022A, and CN111636022A. Among them, the cost of rare earth elements is also high, which restricts their large-scale application; Ti and V are both hydrogen-absorbing elements, which can form solid solutions in any proportion and generally have a large hydrogen absorption capacity. Moreover, through the substitution of Ti, the cost of the alloy can be effectively reduced.
[0004] From the perspective of cost and large-scale application, it is still necessary to give priority to cheaper industrial-grade ferrovanadium alloys (FeV50, FeV80) instead of pure V to further significantly reduce the cost of the alloy. The cost of raw materials of ferrovanadium alloy is only 5% of pure vanadium, but Al, Si, and O in ferrovanadium alloy have a great influence on the hydrogen storage performance of the alloy. For example, the introduction of Si in ferrovanadium alloy will lead to the appearance of Laves second phase in the alloy, the hydrogen storage capacity of the alloy will be reduced, the platform pressure will be increased, and the platform slope will be increased. The introduction of Al will also reduce the hydrogen storage capacity of the alloy and increase the platform pressure. In addition, ferrovanadium hydrogen storage alloys are usually prepared by aluminothermic reaction, which is violent and dangerous, and it will also make it difficult to disperse the doped elements evenly in the ferrovanadium matrix. Therefore, complex smelting and heat treatment operations are also required.
[0005] Therefore, it is necessary to provide an alloy material with low cost, simple preparation process and excellent hydrogen storage performance. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned defects existing in the prior art, take ferrovanadium alloy as the matrix, adopt specific elements for refining and doping, and further optimize the heat treatment process to reduce the content of impurity elements in the ferrovanadium alloy, and effectively improve the hydrogen storage performance of the hydrogen storage alloy, for example, improve the maximum hydrogen absorption and effective dehydrogenation amount of the hydrogen storage alloy.
[0007] To achieve the above object, the present invention adopts the following technical solution: In a first aspect of the present invention, a high-capacity hydrogen storage alloy is provided, the element composition of which comprises: Ti a Cr b (FeV+zwt.%RE) x M y , wherein FeV represents vanadium-iron alloy; RE represents a rare earth element, z represents the doping amount of the rare earth element; M includes at least one element selected from Mn, Co, Ni, Cu, Zr, Zn, Al, and Mo; a, b, x, and y represent the atomic numbers of Ti, Cr, FeV, and M, respectively, a+b+x+y=100, 10≤a≤60, 0≤b≤70, 10≤x≤70, 0≤y≤10, and 0≤z≤10; the high-capacity hydrogen storage alloy is prepared according to a method comprising the following steps: S1, in an inert atmosphere, mixes the raw materials of ferrovanadium alloy and rare earth elements uniformly, and performs arc refining at a current of 50-300A to obtain refined ferrovanadium alloy, which is marked as FeV-RE; S2: maintaining an inert atmosphere, uniformly mixing the FeV-RE, Ti source, Cr source, and M source prepared in step S1, and arc melting at a current of 50-300A to obtain a cast alloy; S3 is heated to 1200-1400°C in two stages for heat treatment for 5-15 minutes. After quenching and removal of the surface oxide layer, the high-capacity hydrogen storage alloy can be obtained. The specific process of heat treatment is: firstly heating to 800-1000°C at a rate of 10-30°C / min; then heating to 1200-1400°C at a rate of 3-10°C / min, and the heating rates of the two stages are different.
[0008] The present invention develops a low-cost, high-performance, easily activated single BCC structure hydrogen storage alloy based on a Ti-Cr-V based hydrogen storage alloy with a BCC structure. The content of impurity elements in the vanadium-iron alloy is reduced through rare earth refining, metal element substitution and heat treatment process optimization, and the uniformity of each component in the alloy can be effectively improved, thereby effectively improving the maximum hydrogen absorption and effective dehydrogenation of the hydrogen storage alloy.
[0009] Preferably, the ferrovanadium alloy includes at least one of FeV80 and FeV50.
[0010] Preferably, the RE includes at least one of La, Ce, Y, Nd, Sc, Pr, Eu, Gd, Tb, Dy and Ho. RE represents a rare earth metal element, which can not only be used as an impurity remover to remove impurities such as Al, Si and O in the ferrovanadium alloy, but also can be used as a second phase, dispersed in the ferrovanadium alloy system, to improve the hydrogen storage performance.
[0011] Preferably, in the element composition of the hydrogen storage alloy, the amount ratio of Ti and Cr satisfies: 0.7≤a / b≤1.4. Ti can be miscible with vanadium-based alloys in any proportion. The addition of Cr, as a hydrogen-unstable element, has a low affinity for hydrogen, and hydrogen is very easy to move in it, which plays a role in regulating the heat of formation and decomposition pressure. In theory, it increases the hydrogen desorption platform pressure of the hydrogen storage alloy, thereby facilitating the reversibility of the alloy's hydrogen absorption and desorption. In the above alloy of the present invention, the amount ratio of Ti and Cr is within the above appropriate range, and the hydrogen storage alloy has a suitable hydrogen absorption / desorption platform pressure.
[0012] Preferably, the inert atmosphere is an atmosphere formed by at least one gas selected from the group consisting of nitrogen, helium and argon.
[0013] Preferably, the Ti source includes Ti element.
[0014] Preferably, the Cr source includes simple Cr.
[0015] Preferably, the M source includes a metal single substance of the M element.
[0016] Preferably, the raw material of the rare earth element includes at least one of a rare earth metal element and a rare earth metal oxide, and more preferably a rare earth metal element.
[0017] Preferably, the refining time in step S1 is 8-30 min.
[0018] Preferably, the smelting in step S2 is carried out in a vacuum state using a vacuum non-consumable arc furnace or a vacuum induction furnace, the vacuum degree is drawn to an absolute pressure of ≤0.005MPa, and then an inert protective gas is filled to a relative pressure of ≥-0.05MPa. When a vacuum non-consumable arc furnace is used, the current of the arc melting is 50-300A. In order to make the elements in the alloy evenly distributed, the smelting can be carried out for a short time and multiple times.
[0019] Preferably, the inert protective gas includes at least one of helium, nitrogen and argon.
[0020] Preferably, the smelting may be short-term and repeated smelting to ensure uniform distribution of the components in the alloy. For example, the smelting time may be 1-5 min / time, and usually 3-5 repeated smeltings are performed to achieve uniform distribution.
[0021] Preferably, the quenching medium in step S3 is a NaCl solution with a concentration of 0-20%. It should be noted that when the concentration is 0wt.%, it means that the quenching medium is water.
[0022] The commonly used methods for removing oxides on the surface of alloys in the art can be used in the present invention. Optionally, the operation of removing the surface oxide layer in step S3 includes at least one of mechanical grinding and chemical etching.
[0023] The second aspect of the present invention further provides a method for preparing the high-capacity hydrogen storage alloy according to the first aspect of the present invention, comprising the following steps: S1, in an inert atmosphere, mixes the raw materials of ferrovanadium alloy and rare earth elements uniformly, and performs arc refining at a current of 50-300A to obtain refined ferrovanadium alloy, which is marked as FeV-RE; S2: maintaining an inert atmosphere, uniformly mixing the FeV-RE, Ti source, Cr source, and M source prepared in step S1, and arc melting at a current of 50-300A to obtain a cast alloy; S3 is heated to 1200-1400°C in two stages for heat treatment for 5-15 minutes. After quenching and removal of the surface oxide layer, the high-capacity hydrogen storage alloy can be obtained. The specific process of heat treatment is: firstly heating to 800-1000°C at a rate of 10-30°C / min; then heating to 1200-1400°C at a rate of 3-10°C / min, and the heating rates of the two stages are different.
[0024] Rare earth elements are first refined with ferrovanadium alloy to form a dispersed second phase in the ferrovanadium alloy, and the impurity elements in the ferrovanadium alloy are absorbed and accommodated in the phase, thereby reducing their migration performance in the ferrovanadium alloy and preventing their influence on the hydrogen storage performance of the alloy; at this time, further smelting is carried out with the doped metal elements, and the second phase of rare earth elements can promote the metal elements to be uniformly doped into the ferrovanadium alloy phase, replace the relevant lattice sites, and enhance the hydrogen storage activity of the alloy; at this time, two lattice structures, BCC+Laves phase, are formed in the ferrovanadium-based phase in the alloy, and further heat treatment and quenching treatment and other processes can be carried out to obtain a pure single BCC phase hydrogen storage alloy material.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses ferrovanadium alloy as the matrix, uses rare earth refined ferrovanadium alloy, and metal element doping, and further optimizes the heat treatment process to reduce the content of impurity elements in the ferrovanadium alloy, effectively improving the hydrogen storage performance of the hydrogen storage alloy. The maximum hydrogen absorption capacity of the prepared hydrogen storage alloy at 25°C and 9MPa is above 3.3wt.%; the effective hydrogen absorption capacity is above 2 wt.%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The PCT curves of hydrogen absorption and desorption of the hydrogen storage alloy materials of Example 1 and Comparative Example 1; Figure 2 is the XRD spectrum of the hydrogen storage alloy material of Example 1; Figure 3 is the XRD spectrum of the hydrogen storage alloy material of Comparative Example 1; Figure 4 This is the XRD spectrum of the hydrogen storage alloy material of Comparative Example 2. DETAILED DESCRIPTION
[0027] For better explanation of the purpose, technical scheme and advantage of the present invention, the present invention will be further described below in conjunction with specific embodiment and accompanying drawing, but embodiment does not limit the present invention in any form.Unless otherwise specified, the reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art.Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0028] Example 1 This embodiment provides a high-capacity hydrogen storage alloy, the target element composition of the alloy is Ti 44 Cr 37 (FeV50+5wt.%Ce) 14 Mo5, the preparation method comprises the following steps: S1 first weighs vanadium iron alloy FeV50 and pure cerium, mixes them evenly, and then refines them in an electric arc furnace in an argon atmosphere at a current of 150 A for 2 min / time. After refining for 4 times, a refined vanadium iron alloy is obtained, which is marked as FeV50+5wt.%Ce; S2 metal Ti, Cr, and FeV50+5wt.%Ce obtained by refining in step S1, according to Ti 44 Cr 37 (FeV50) 14 The alloy composition of Mo5 was prepared, and the cast alloy Ti was obtained by melting 4 times in an arc furnace with a current of 150A in an argon atmosphere, each melting for 120s. 44 Cr 37 (FeV50+5wt.%Ce) 14 Mo5; S3: the cast alloy Ti obtained in step S2 44 Cr 37 (FeV50+5wt.%Ce) 14 After Mo5 is coated with 0.05 mm thick tantalum foil, it is placed in a quenching furnace under inert atmosphere protection for heat treatment and quenching, wherein the heating procedure of the heat treatment is: firstly heating to 1000°C at a heating rate of 10°C / min, then heating to 1300°C at a heating rate of 5°C / min, keeping warm for 10 minutes, and then quickly transferring to a 5wt.% NaCl aqueous solution for quenching; the quenched gold ingot is polished with a grinding wheel to remove the oxide layer on the surface of the gold ingot, thereby obtaining the high-capacity hydrogen storage alloy.
[0029] Example 2 This embodiment provides a high-capacity hydrogen storage alloy, the target element composition of the alloy is Ti 31 Cr 35 (FeV80+3wt.%Ce) 34 , the preparation method comprises the following steps: S1 first weighs vanadium iron alloy FeV80 and pure cerium, mixes them evenly, and then refines them in an arc furnace in an argon atmosphere at a current of 150A for 2 minutes per time. After refining for 4 times, a refined vanadium iron alloy is obtained, which is marked as FeV80+3wt.%Ce; S2 metal Ti, Cr, and FeV80+3wt.%Ce obtained by refining in step S1, according to Ti 31 Cr 35 (FeV80) 34 The alloy composition was prepared and the cast alloy Ti was obtained by melting 4 times in an arc furnace with a current of 150A in an argon atmosphere for 120s each time. 31 Cr 35 (FeV80+3wt.%Ce)34 ; S3: the cast alloy Ti obtained in step S2 31 Cr 35 (FeV80+3wt.%Ce) 34 After being coated with 0.05 mm thick tantalum foil, the alloy is placed in a quenching furnace under inert atmosphere protection for heat treatment and quenching, wherein the heating procedure of the heat treatment is: firstly heating to 1000°C at a heating rate of 10°C / min, then heating to 1300°C at a heating rate of 5°C / min, keeping warm for 10 minutes, and then quickly transferring to water for quenching; the alloy ingot after quenching is polished with a grinding wheel to remove the oxide layer on the surface of the gold ingot, thereby obtaining the high-capacity hydrogen storage alloy.
[0030] Example 3 This embodiment provides a high-capacity hydrogen storage alloy, the target element composition of the alloy is Ti 31 Cr 30 Mn5(FeV80+5wt.%Y) 34 The preparation method comprises the following steps: S1 first weighs vanadium iron alloy FeV80 and pure yttrium, mixes them evenly, and then refines them in an arc furnace in an argon atmosphere at a current of 170A for 2 minutes each time. After refining for 4 times, a refined vanadium iron alloy is obtained, which is marked as FeV80+5wt.%Y; S2 metal Ti, Cr, Mn and FeV80+5wt.%Y obtained by refining in step S1, according to Ti 31 Cr 30 Mn5(FeV80) 34 The alloy composition was prepared, and the cast alloy Ti was obtained by melting 4 times in an arc furnace with a current of 200A in an argon atmosphere, each melting for 120s. 31 Cr 30 Mn5(FeV80+5wt.%Y) 34 ; S3: the cast alloy Ti obtained in step S2 31 Cr 30 Mn5(FeV80+5wt.%Y) 34 After being coated with 0.05 mm thick tantalum foil, the gold ingot is placed in a quenching furnace under inert atmosphere protection for heat treatment and quenching, wherein the heating procedure of the heat treatment is: firstly heating to 1000°C at a heating rate of 10°C / min, then heating to 1300°C at a heating rate of 5°C / min, keeping warm for 10 minutes, and then quickly transferring to water with a concentration of 500°C for quenching; the quenched gold ingot is polished with a grinding wheel to remove the oxide layer on the surface of the gold ingot, thereby obtaining the high-capacity hydrogen storage alloy.
[0031] Embodiment 4-11 A series of high-capacity hydrogen storage alloys with different elemental compositions are provided. The target elemental composition of the alloys is shown in Table 1. The preparation method is the same as that of Example 1.
[0032] Comparative Example 1 This comparative example provides a hydrogen storage alloy, which has the same elemental composition as that of Example 1 and is prepared by referring to the method of Example 1. The difference from Example 1 is that step S3 is not performed.
[0033] Comparative Example 2 This comparative example provides a hydrogen storage alloy having the same elemental composition as that of Example 1 and is prepared by referring to the method of Example 1. The difference from Example 1 is that in step S3, after the temperature is raised to 1000°C, no further temperature increase is performed, and the alloy is kept at 1000°C for 10 minutes and then quenched.
[0034] Comparative Example 3 This comparative example provides a hydrogen storage alloy, which has the same elemental composition as that of Example 1 and is prepared by referring to the method of Example 1. The difference from Example 1 is that step S1 is not performed, and the target alloy composition Ti is obtained. 44 Cr 37 (FeV50+5wt.%Ce) 14 Mo5 is prepared by batching from step S2.
[0035] Comparative Example 4 This comparative example provides a hydrogen storage alloy, which is prepared by referring to the method of Example 1. The difference from Example 1 is that Ce is not added in step S1, and the target alloy composition Ti is directly added in step S2. 44 Cr 37 (FeV50) 14 Mo5 for batching and smelting, the element composition of the hydrogen storage alloy is Ti 44 Cr 37 (FeV50) 14 Mo5.
[0036] Comparative Example 5 This comparative example provides a hydrogen storage alloy, which is prepared by referring to the method of Example 1. The difference from Example 1 is that step S1 is not performed, and the target alloy composition Ti is directly obtained. 44 Cr 37 (FeV50) 14 Mo5 is prepared by batching from step S2.
[0037] The hydrogen storage performance of the hydrogen storage alloys obtained in the above examples and comparative examples was characterized, and the specific test items, test methods and results are as follows: 1. Use XRD to characterize the phase structure of hydrogen storage alloys.
[0038] 2. Hydrogen storage performance test: The hydrogen storage alloys prepared in the above embodiments and comparative examples were activated at room temperature. The activation conditions were as follows: 9 MPaH2 was charged at room temperature and then dehydrogenated at 400°C for 1 h; then a hydrogen absorption kinetics test was performed at 25°C and 9 MPa, with the equilibrium pressure of the hydrogen desorption system being 0.1 MPa, and a cycle performance test was performed. The test results are shown in Table 1.
[0039] Table 1 Test results of hydrogen storage alloys obtained in Examples and Comparative Examples From the above results we can see that: The present invention uses ferrovanadium as a matrix, adopts rare earth refined ferrovanadium, and metal element doping, and further optimizes the heat treatment process to reduce the content of impurity elements in the ferrovanadium, effectively improving the hydrogen storage performance of the hydrogen storage alloy, such as improving the maximum hydrogen absorption and effective dehydrogenation amount of the hydrogen storage alloy.
[0040] The maximum hydrogen absorption capacity of the prepared hydrogen storage alloy at 25°C and 9MPa is above 3.3wt.%; the effective hydrogen absorption capacity is above 2wt.%.
[0041] Comparison between Comparative Examples 1 and 2 and Example 1 shows that the heat treatment process after arc melting has a greater impact on the phase structure of the alloy. Without two-stage heating, the prepared alloy may contain BCC phase and Laves phase, resulting in an increase in the slope factor of the hydrogen desorption platform and a decrease in the amount of hydrogen absorption and desorption.
[0042] In Comparative Examples 3-5, rare earth was not used to refine the ferrovanadium alloy first, resulting in the presence of more impurities in the ferrovanadium alloy matrix, which significantly reduced the hydrogen absorption capacity of the hydrogen storage alloy.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high capacity hydrogen storage alloy, characterized in that: The element composition of the hydrogen storage alloy includes: Ti a Cr b (FeV+zwt.%RE) x M y , wherein FeV represents ferrovanadium; RE represents a rare earth element, and z represents the doping amount of the rare earth element; M includes at least one element selected from Mn, Co, Ni, Cu, Zr, Zn, Al, and Mo; a, b, x, and y represent the atomic numbers of Ti, Cr, FeV, and M, respectively, and a+b+x+y=100, 10≤a≤60, 0≤b≤70, 10≤x≤70, 0≤y≤10, and 0≤z≤10; The high-capacity hydrogen storage alloy is prepared according to a method comprising the following steps: S1, in an inert atmosphere, mixes the raw materials of ferrovanadium alloy and rare earth elements uniformly, and performs arc refining at a current of 50-300A to obtain refined ferrovanadium alloy, which is marked as FeV-RE; S2: maintaining an inert atmosphere, uniformly mixing the FeV-RE, Ti source, Cr source, and M source prepared in step S1, and arc melting at a current of 80-300A to obtain a cast alloy; S3 is heated to 1200-1400°C in two stages for heat treatment for 5-15 minutes. After quenching and removal of the surface oxide layer, the high-capacity hydrogen storage alloy can be obtained. The specific process of heat treatment is: firstly heating to 800-1000°C at a rate of 10-30°C / min; then heating to 1200-1400°C at a rate of 3-10°C / min, and the heating rates of the two stages are different.
2. The high-capacity hydrogen storage alloy according to claim 1, characterized in that The vanadium-iron alloy includes at least one of FeV80 and FeV50.
3. The high-capacity hydrogen storage alloy according to claim 1, characterized in that The RE includes at least one of La, Ce, Y, Nd, Sc, Pr, Eu, Gd, Tb, Dy, and Ho.
4. The high-capacity hydrogen storage alloy according to claim 1, characterized in that In the element composition of the hydrogen storage alloy, the usage ratio of Ti and Cr satisfies: 0.7≤a / b≤1.
4.
5. The high-capacity hydrogen storage alloy according to claim 1, characterized in that: The inert atmosphere is an atmosphere formed by at least one gas selected from the group consisting of nitrogen, helium, and argon.
6. The high-capacity hydrogen storage alloy according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The Ti source includes Ti element; (2) The Cr source includes Cr element; (3) The M source includes a metal single substance of the M element; (4) The raw material of the rare earth element includes at least one of a rare earth metal element and a rare earth metal oxide.
7. The high-capacity hydrogen storage alloy according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The refining time in step S1 is 8-30 min; (2) The smelting time in step S2 is 8-30 min; (3) The quenching medium in step S3 is a NaCl solution with a concentration of 0-20 wt.%.
8. The high capacity hydrogen storage alloy according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The operation of removing the surface oxide layer in step S3 includes at least one of mechanical grinding and chemical etching; (2) The smelting in step S2 is carried out in a vacuum state using a vacuum non-consumable arc furnace or a vacuum induction furnace, the vacuum degree is evacuated to an absolute pressure of ≤0.005 MPa, and then an inert protective gas is filled to a relative pressure of ≥-0.05 MPa.
9. The high-capacity hydrogen storage alloy according to claim 1, characterized in that: The maximum hydrogen absorption capacity of the hydrogen storage alloy at 25° C. and 9 MPa is greater than 3.3 wt.%; the effective hydrogen absorption capacity of the hydrogen storage alloy at 65° C. and 0.1 MPa is greater than 2 wt.%.
10. The method for preparing a high-capacity hydrogen storage alloy according to any one of claims 1 to 9, characterized in that: The steps include: S1, in an inert atmosphere, mixes the raw materials of ferrovanadium alloy and rare earth elements uniformly, and performs arc refining at a current of 50-300A to obtain refined ferrovanadium alloy, which is marked as FeV-RE; S2: maintaining an inert atmosphere, uniformly mixing the FeV-RE, Ti source, Cr source, and M source prepared in step S1, and arc melting at a current of 80-300A to obtain a cast alloy; S3 is heated to 1200-1400°C in two stages for heat treatment for 5-15 minutes. After quenching and removal of the surface oxide layer, the high-capacity hydrogen storage alloy can be obtained. The specific process of heat treatment is: firstly heating to 800-1000°C at a rate of 10-30°C / min; then heating to 1200-1400°C at a rate of 3-10°C / min, and the heating rates of the two stages are different.
Citation Information
Patent Citations
Titanium-based hydrogen storage alloy improved by vanadium iron and preparation method thereof
CN105063425A
V-Fe based solid solution type hydrogen storage alloy and preparation method thereof
CN106801177A
Multi-element hydrogen storage alloy and preparation method thereof
CN118007003A
Rare earth AB2 type hydrogen storage alloy as well as preparation method and application thereof
CN119307760A
Hydrogen-occluding alloy and method for production thereof
US20040037733A1
Cited By
High-entropy hydrogen storage alloy and preparation method thereof
CN119956189A
High-entropy hydrogen storage alloy and preparation method thereof
CN119956189B
Rare earth-rich high-capacity vanadium-based solid solution type hydrogen storage alloy and preparation method thereof
CN121087339A
AB2 type hydrogen storage alloy as well as preparation method and application thereof
CN121592892A